ChemInform Abstract: Palladium‐Catalyzed Synthesis of (Hetero)Aryl Alkyl Sulfones from (Hetero)Aryl Boronic Acids, Unactivated Alkyl Halides, and Potassium Metabisulfite. Issue 11 (February 2016) - Shavnya, Andre; Hesp, Kevin D.; Mascitti, Vincent; Smith, Aaron C.
Abstract: A direct synthesis of aryl alkyl sulfones is achieved by Pd‐catalyzed reaction of arylboronic acids, alkyl halides, and potassium metabisulfite as source of the SO2 ‐unit.